The application of bentonite and zeolite for soil amelioration in acidic sandy soil - Tállai, Magdolna (Acta Agraria Debreceniensis, 2009)
In a pot experiment, we have studied the effect of bentonite and zeolite in different dosages [control; 5; 10; 15; 20 g kg-1] on acidic (pHH2O=5.65) humus sandy soil. The experiment was set up in 2007 and 2008 in the greenhouse of the UD CASE Department of Agrochemistry and Soil Science. As a test plant, perennial ryegrass (Lolium perenne L.) was used. In laboratory examinations, pH(H2O), pH(KCl), hidrolytic acidity, nitrate-N content, readily available phosphorus and potassium content were determined. Among soil microbial parameters, the total number of bacteria, the cellulose-decomposing bacteria, the carbon-dioxide production, the microbial biomass-C content of soil, and the saccharase enzyme activity were measured. In the experiment the biomass of the test plant was determined.The effect of bentonite and zeolite in different dosages can be summarized as follows:− The pH increased under the effect of low dosages. With the increasing of the pH the hydrolytic acidity - at the bentonite treatments significantly – decreased. − Regarding the readily available nutrient content of the soil, low and medium dosages proved to be effective. High dosages of bentonite treatments reduced the nitrate-N content, the readily available phosphorus, and potassium content of soil, by zeolite treatments the high dosages reduced the nitrate-N content of soil. − Regarding the measured soil microbial parameters in both treatments low and medium dosages proved to be also effective, but the high dosages didn’t cause decreasing at the total number of bacteria, and by zeolite treatments the biomass-C content of soil.− Also the bentonite and zeolite treatments enlarged the biomass of the test plant. We experienced significant increasing by bentonite treatments by the effect of medium and high dosages, while in zeolite treatments only the high dosage caused significantly increasing in plant biomass. The largest dosages decrease the plant biomass. − Under the statistical analysis we found many medium and tight correlation between the studied parameters.